2020
DOI: 10.1155/2020/6806857
|View full text |Cite
|
Sign up to set email alerts
|

Persistent High-Risk HPV Infection and Molecular Changes Related to the Development of Cervical Cancer

Abstract: This article is a preliminary investigational study that is aimed at giving hints about the interesting biomarkers involved in the transition process from low-grade cervix lesion to invasive cervical cancer. Our study focuses on the risk factors and tumour molecular changes in one patient. First in 1986, she was diagnosed a preinvasive cervix lesion. Then, 16 years later, she was diagnosed an invasive cervical cancer. The 2002 diagnosis was a squamous cell carcinoma of the cervix, stage IIIB (FIGO), whereas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Although 70% of sexually active individuals are infected with HPV, the infection usually clears up within a few months, with 90% of cases clearing within two years after HPV acquisition [5]. However, 10 to 20% of HPV infections persist latently, leading to disease progression and eventually invasive cancer [6]. HPV messenger ribonucleic acid (mRNA) tests determine whether the virus is actively expressing the proteins responsible for oncogenesis in HPV infection [7] and thus allow the identification of transient and potentially transforming HPV infections [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although 70% of sexually active individuals are infected with HPV, the infection usually clears up within a few months, with 90% of cases clearing within two years after HPV acquisition [5]. However, 10 to 20% of HPV infections persist latently, leading to disease progression and eventually invasive cancer [6]. HPV messenger ribonucleic acid (mRNA) tests determine whether the virus is actively expressing the proteins responsible for oncogenesis in HPV infection [7] and thus allow the identification of transient and potentially transforming HPV infections [8].…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factor of cervical cancer is persistent HPV infection. It promotes impaired growth and differentiation of cells, leading to dysplasia (cervical intraepithelial neoplasia, CIN) [4]. We distinguished three grades of cervical dysplasia: CIN1 (LSIL; low-grade squamous intraepithelial lesion), CIN2, and CIN3 (classified together as HSIL; high-grade squamous intraepithelial lesion).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent infection with high‐risk human papillomavirus (HPV) genotypes is considered as the major cause of cervical cancer 4–6 . HPV infection may induce genomic alterations, such as copy number variation, DNA methylation, and somatic DNA mutation, which eventually contribute to cervical carcinogenesis 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Persistent infection with high‐risk human papillomavirus (HPV) genotypes is considered as the major cause of cervical cancer. 4 , 5 , 6 HPV infection may induce genomic alterations, such as copy number variation, DNA methylation, and somatic DNA mutation, which eventually contribute to cervical carcinogenesis. 7 , 8 In addition to the abnormalities at transcriptome and epigenetic levels, recent studies have indicated that dysregulation of posttranscriptional splicing variants (alternative splicing) may also be associated with cervical cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%